Legal Responsibility For Operational Failures Through Robotic Telesurgery - Ni Putu Eka Madeni Apriliani; I Nyoman Bagiastra (West Science Interdisciplinary Studies, 2024)
Technological developments, especially in the health sector, are currently growing very rapidly. Robotic Telesurgery or remote surgical robots are expected to become a technology that can realize health equality in Indonesia, but it is a shame that technological progress is not comparable to the relevant regulations that regulate it, it is feared that this will not guarantee legal certainty which could lead to malpractice. The method used in this research is a normative legal research method because the focus of the study departs from the vagueness of norms using the approach: statute approach, conceptual approach, as well as analytical approach. The legal material search technique uses document study techniques, and study analysis uses qualitative analysis. The results of this research are that there is a void in norms in Law Number 17 of 2023 concerning Health which does not regulate legal responsibility for failed operations through Robotic Telesurgery So it is necessary to create a law that specifically regulates the responsibilities of doctors.